2021
DOI: 10.47605/tapro.v10i1.246
|View full text |Cite
|
Sign up to set email alerts
|

FIRST RECORD OF Pareas vindumi VOGEL, 2015 (REPTILIA: PAREIDAE) FROM CHINA WITH A REVISION TO MORPHOLOGY

Abstract: We report the first record of the poorly known slug-eating snake, Pareas vindumi from China: a female specimen collected from Dazhuba ranger station, Gaoligongshan National Nature Reserve, Tengchong city, Yunnan Province. The newly collected specimen represents only the second known specimen of the species and provides the first and valuable data on its morphological variation. Based on the new specimen, we revise the diagnostic characteristics of the species and provide additional data on its natural history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…As the type locality of P. macularius is located in Mon State, Myanmar, this raises the question of the taxonomic status of the populations from Laos (this work is currently in progress and will be presented elsewhere). Within P. hamptoni species group we confirm the results of Ding et al (2020) and Yang et al (2021) , suggesting that P. kaduri and P. nigriceps are sister taxa, while the phylogenetic position of P. vindumi remains unresolved. Genetic divergence among the three members of the Taiwan – Ryukyus clade of this group ( P. atayal , P. komaii , and P. iwasakii ) is comparatively low (6.9% < p < 9.0% in cyt b gene; see Table S7 ), and the basal radiation of this clade is estimated to happen only ca.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…As the type locality of P. macularius is located in Mon State, Myanmar, this raises the question of the taxonomic status of the populations from Laos (this work is currently in progress and will be presented elsewhere). Within P. hamptoni species group we confirm the results of Ding et al (2020) and Yang et al (2021) , suggesting that P. kaduri and P. nigriceps are sister taxa, while the phylogenetic position of P. vindumi remains unresolved. Genetic divergence among the three members of the Taiwan – Ryukyus clade of this group ( P. atayal , P. komaii , and P. iwasakii ) is comparatively low (6.9% < p < 9.0% in cyt b gene; see Table S7 ), and the basal radiation of this clade is estimated to happen only ca.…”
Section: Resultssupporting
confidence: 80%
“…Several recent taxonomic studies on Pareas have demonstrated that this genus has a high level of hidden and yet undescribed diversity ( e.g . You, Poyarkov & Lin, 2015 ; Bhosale et al, 2020 ; Vogel et al, 2020 , 2021 ; Ding et al, 2020 ; Liu & Rao, 2021 ; Yang et al, 2021 ). Out of 26 currently recognized species of Pareas (including those described in this work), twelve species were discovered within the last twelve years ( Uetz, Freed & Hošek, 2021 ), of which eleven species were described based on an integrative evidence from morphological and molecular data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured the body and tail lengths with a measuring tape (to the nearest of 1 mm). For comparison, we examined the type specimens of Pareas yunnanensis, data for other species of Pareas were taken from the original and subsequent descriptions (Boulenger 1900(Boulenger , 1905Vogt 1922;Pope 1935;Zhao et al 1998;Grossmann & Tillack 2003;Guo & Deng 2009;Guo et al 2011;Loredo et al 2013;Vogel 2015;You et al 2015;Hauser 2017;Bhosale et al 2020;Ding et al 2020;Vogel et al 2020Vogel et al , 2021Wang et al 2020;Le et al 2021;Liu & Rao 2021;Yang et al 2021;Poyarkov et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Pareas Wagler, 1830 is a genus of small and slender arboreal nocturnal snakes with a blunt snout, missing mental groove, and no teeth on the anterior part of maxillary, as they feed on snails or slugs; they are also known as snail-eating or slug-eating snakes (Hoso et al 2007;Wallach et al 2014;You et al 2015;Poyarkov et al 2022). The genus Pareas now contains 26 recognized species (Le et al 2021;Liu & Rao 2021;Vogel et al 2021;Poyarkov et al 2022;Uetz et al 2022), of which 20 species are distributed in China (Bhosale et al 2020;Ding et al 2020;Liu & Rao 2021;Vogel et al 2020Vogel et al , 2021Yang et al 2021;Poyarkov et al 2022). Two subgenera are at present recognized within the genus: the subgenus Pareas includes six species distributed mostly in Indochina and Sundaland, whereas the subgenus Eberhardtia Angel, 1920 includes the remaining species and has a wider distribution, covering northeastern India, Myanmar, southern and eastern China, and southwards to Sumatra (Poyarkov et al 2022).…”
Section: Introductionmentioning
confidence: 99%